Some aspects of the law of gaming in Malaysia / Sharizat Abdul Jalil - Sharizat, Abdul Jalil (1976)
The subject of gambling has baffled and intrigued the writer for a very long time. What could have been a much more presentable paper was, however, foiled by the writer's deep ignorance of the very essence of gambling, i.e. how to gamble. Had the writer known of this important prereguisite she would probably have refrained from "meddling" in it. However, after starting out with high aspirations and lofty deals of being a near 'expert' on the subject (even after losing out in the game from the very outset) the writer could not possibly abandon the whole idea. What is finally presented in this paper ls only a small part of what the writer actually gained. To begin with the writer found great difficulty in expressing her thoughts. Gaming may seemingly appear to encompass only the plying of cards and the like. This is not so. It includes, amongst other things, private and public lotteries, betting, Card games and also "legalised gaming" like horse racing, Empat Number Ekor, Social welfare lotteries, Sports Toto etc. Each of these could very well form a topic for a working paper.